Ramadhan Community Service and Strengthening the Community’s Spirituality in Tambang Village, Ponorogo - Siti Musarofah; Ummi Mahmudah (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2022)
The purpose of this KKN activity is to improve the religious experience of the community in order to support spiritual quality and at the same time foster motivation in solving various life problems through a religious approach. Based on the survey and situation analysis, the following problems can be identified: 1) The people of the Tambang Village have minimal religious knowledge, because the number of religious teachers is still lacking. 2) The education level of the younger generation is low, because the interest and ability to continue to a higher level of education is lacking. 3) Agricultural and livestock products are abundant but selling prices are low due to the lack of marketing strategies. As a result, the income of the population is low. The general assumption of this KKN activity is that the target community of KKN will be empowered by the KKN programs offered. The KKN activity program includes: (1) in the religious field, KKN participants provide examples and guidance to the younger generation to become imams of Fardu prayers and tarawih prayers in mosques and musalla (prayer rooms), provide guidance and role models after the tarawih prayers and dawn prayers, provide training and role models to become Friday prayer preacher, providing training on teaching reading and writing of the Qur’an at the TPA. 2) in the field of education, KKN participants motivate the younger generation to continue their education to the tertiary level, 3) in the economic field, provide training on processing fresh cow’s milk into cakes, and provide training on marketing and packaging methods of agricultural products.